2017
DOI: 10.1017/s1478951517000207
|View full text |Cite
|
Sign up to set email alerts
|

A concept analysis in relation to the cultural competency of the palliative care workforce in meeting the needs of young people from South Asian cultures

Abstract: Cultural care should be integral to holistic patient care, irrespective of a person's race or ethnicity. There is an urgent need to involve young BAME patients with palliative care needs and their families in the development of a robust tool to assess cultural competency in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Moreover, in a concept analysis using In line with the justice-oriented nature of CCN, Henderson et al (2018) in a concept analysis, showed that delivery of fair and ethical care is one of the features of CCN. Moreover, the analysis of the concept of CC in palliative care workforce showed that cultural care should be an integral part of comprehensive patient care, regardless of race or ethnicity (Brown et al, 2018). Additionally, in a concept analysis by Suh (2004), the identified features of CCN were openness, flexibility, and ability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a concept analysis using In line with the justice-oriented nature of CCN, Henderson et al (2018) in a concept analysis, showed that delivery of fair and ethical care is one of the features of CCN. Moreover, the analysis of the concept of CC in palliative care workforce showed that cultural care should be an integral part of comprehensive patient care, regardless of race or ethnicity (Brown et al, 2018). Additionally, in a concept analysis by Suh (2004), the identified features of CCN were openness, flexibility, and ability.…”
Section: Discussionmentioning
confidence: 99%
“…6 , 28 This lack of specific research focusing upon ethnically diverse families may in turn deter these families from sharing their experiences. 54 Furthermore, it is important to consider that the neonatal palliative care journey may not only be experienced by the infant’s parents, but other significant family members such as siblings and grandparents who are frequently underrepresented in research. 55 , 56 …”
Section: Whose Voices Are Missing?mentioning
confidence: 99%
“…Palliative care, as an important component of people-oriented health services, aims to alleviate severe suffering related to disease and improve the quality of life, and has become an effective intervention widely used in the treatment of cancer [ 6 ]. However, the development of palliative care for cancer patients in many Asian regions remains incomplete and inadequate [ 7 , 8 ]. The awareness and knowledge of palliative medicine and advanced care planning were at low levels even in the diverse Asian groups living in the United States, which raised concerns and demonstrated the urgent need for appropriate education programs on palliative care in Asia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%